Kinetic energy release in fragmentation processes following electron emission: a time-dependent approach - Chiang, Ying-Chih; Otto, Frank; Meyer, Hans-Dieter; Cederbaum, Lorenz S. (The journal of chemical physics, 2012)
A time-dependent approach for the kinetic energy release (KER) spectrum is developed for a fragmentation of a diatomic molecule after an electronic decay process, e.g., Auger process. It allows one to simulate the time-resolved spectra and provides more insight into the molecular dynamics than the time-independent approach. Detailed analysis of the time-resolved emitted electron and KER spectra sheds light on the interrelation between wave packet dynamics and spectra.